2023
DOI: 10.1097/dcr.0000000000002885
|View full text |Cite
|
Sign up to set email alerts
|

Excisional Hemorrhoidectomy Versus Dearterialization With Mucopexy for the Treatment of Grade 3 Hemorrhoidal Disease: the EMODART3 Multicenter Study

Antonio Giuliani,
Lucia Romano,
Stefano Necozione
et al.

Abstract: BACKGROUND: In the last decades, several surgical approaches have been proposed to treat hemorrhoids. OBJECTIVE: This multicenter study aims to compare transanal hemorrhoidal artery ligation and conventional excisional hemorrhoidectomy for grade III hemorrhoidal disease. DESIGN: Multicenter retrospective study. SETTINGS: Any center belonging to the Italian Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A recent multicentre study reported benefits from Doppler-guided MHD using a THD device with a 9.5% recurrence and 7% reoperation rate ( 29 , 31 , 32 ). Giuliani et al reported that MHD is a safe and efficient technique, especially for third-degree HD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicentre study reported benefits from Doppler-guided MHD using a THD device with a 9.5% recurrence and 7% reoperation rate ( 29 , 31 , 32 ). Giuliani et al reported that MHD is a safe and efficient technique, especially for third-degree HD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%